2015
DOI: 10.1111/ddg.12617
|View full text |Cite
|
Sign up to set email alerts
|

S1 guideline on occupational skin products: protective creams, skin cleansers, skin care products (ICD 10: L23, L24) – short version

Abstract: Job-related hand dermatitis heads up the list of reported occupational diseases. So-called skin products - understood to mean protective creams, skin cleansers and skin care products - are used for the primary and secondary prevention of job- related hand dermatitis. In the interests of evidence-based medicine, the only preventive measures and/or occupational skin products that should be used are those whose potential uses and efficacy are underpinned by scientific research. To this end, the Arbeitsgemeinschaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 93 publications
0
18
1
6
Order By: Relevance
“…In line with this, a prospective intervention study by Kütting et al demonstrated that skin conditions in metalworkers improved most when using both skin care products and barrier creams, followed by using barrier creams alone . However, there is an ongoing discussion whether barrier creams are truly effective in prevention of HE …”
Section: Discussioncontrasting
confidence: 94%
“…In line with this, a prospective intervention study by Kütting et al demonstrated that skin conditions in metalworkers improved most when using both skin care products and barrier creams, followed by using barrier creams alone . However, there is an ongoing discussion whether barrier creams are truly effective in prevention of HE …”
Section: Discussioncontrasting
confidence: 94%
“…Practical literature‐based recommendations referring to this are summarized in Table 6. Regarding barrier creams, evidence for their efficacy 65,66 is limited. They may only be effective against certain irritants and may sometimes even intensify the irritant skin response 67–69 .…”
Section: Preventionmentioning
confidence: 99%
“…71 this strategy is supported by a few controlled prospective studies in apprentices. 27,38,66,[68][69][70][71][72][73][74] Individuals with previous or current AD are particular at risk for development of OHE, however, primary information should be given to everyone. With regard to secondary prevention of work-related HE, some interventions based on health education and ready access to personal protective equipment failed to show a clear benefit.…”
Section: 202206mentioning
confidence: 99%
See 1 more Smart Citation
“…Zur Erfassung einer atopischen Hautdiathese ist die Erhebung des Erlanger Atopie-Scores hilfreich [11]. Eine Pricktestung oder eine Bestimmung spezifischer IgE-Antikörper auf häufige Inhalationsallergene können ergänzend erfolgen, um ggf.…”
Section: Atopie-screeningunclassified